Changes in Rohu (Labeo rohita) Actomyosin During Frozen Storage: Protein Denaturation or Coagulation? - Rao, Shrinivas B. (Fishery Technology, 2025)
Changes taking place in actomyosin extracted from Labeo rohita (Rohu) during storage at -20<’C were studied with a view to find out whether these changes were denaturation or coagulation of proteins. Changes in solubility, Ca2* ATPase activity and Mg2* ATPase activity were monitored for a period of 10 weeks. The irreversible loss of solubility and Caz* and Mg2* ATPase activities indicate that an irreversible aggregation of proteins, probably through covalent disulphide bonds is taking place during frozen storage of rohu actomyosin and this is suggestive of protein coagulation, as distinct from protein denaturation.